Self-Regulated Learning in Online-Based Teacher Education And Training Programs - Wawan Krismanto; Lilik Tahmidaten (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2022)
The era of the coronavirus disease pandemic is increasingly driving the process of transforming teacher education and training from face-to-face to online-based. Besides having flexibility and accessibility, in practice, the transformation process has several weaknesses and challenges. One of them is a culture of self-regulated learning from the participating teachers. For this reason, the purpose of this article is to review self-regulated learning in online-based teacher education and training programs with key questions- how important is self-regulated learning in online-based teacher education and training programs? and how to facilitate the development of self-regulated learning in online-based teacher education and training programs? To answer this, we conducted a literature study of various books and previous research articles, so that the results were complete, both conceptually and empirically. As a result, self-regulated learning has become an important and strategic aspect for the success of any learner or online learning program, including online-based teacher education and training programs. For this reason, every designer, organizer and instructor need to facilitate the development of participants selfregulated learning aspects through their online learning platforms. Although it cannot be assumed that they will automatically and effectively develop their self-regulated learning skills, through deliberate design and facilitation efforts, they need to create and sustain the development of self-regulated learning skills of e-learners through rich learning experiences. Positive self-regulated learning tends to encourage the success of the online-based teacher education and training programs because teachers will give their best efforts to complete their online learning and have the potential to achieve the best results.